Sequências didáticas baseadas na problematização e experimentação sobre os polímeros - Pereira, Valdice Barbosa (2020)
This search aims to analyze the development of didactic sequences elaborated with the approach on polymers, addition reaction, green polymers, biodegradable products and also biopolymers from contextualization. The search was initially held through some questions about the sequence and analysis of chemistry textbooks which are referred to PNLD 2018 in which we noticed some limitations in the sequence of the content discussed. Furthermore, we diagnose that the books are not completed in relation to the methodologies that are presented in a very practical way. In this regard, it was necessary to conduct an adaptation of the issue through the didactic sequence. This sequence has been structured to be developed to in five moments, each one of fifty minutes which is addressed the following teaching methodologies: at first with na exhibiting and diagnose video about previous students’ knowledge, second moment a Flipped Class, third conceptual participative class, fourth problem-based learning and the last one an experimental activity. The sequence was developed to be applied in the second bimester attended by 52 students, from the third year of high school in morning shift. This search took place at Escola Estadual Prof. José Quintella Cavalcanti, located in Arapiraca - AL. The results of the research analysis revealed that the didactic sequence presented different possibilities of dynamics in teachinglearning, such as: a greater involvement and students’ interest in the concepts of chemistry, efficient results in the evaluation process of the subject, raising students' scientific knowledge based on the constructivist ideological and collaborative process. In the face of reaching the search results in order to contribute to the teaching practice, also it has been relevant to a booklet production with the purpose of engaging the teachers’ working with methodologies which are different from the traditional method of teaching. In addition, it has been assumed the contextualization about the polymers topic. In the booklet there are some options that the teachers can work with active methodologies not only in chemistry, but it also in other areas of knowledge promoting an improvement in teaching-learning rates.